Use of Plant Growth Regulators in Tomato (Solanum lycopersicum L.) under Tarai Conditions of Uttarkhand - TIWARI, A. K.; SINGH, D. K. (Indian Journal of Hill Farming, 2015)
Under Uttarakhand conditions a field experiment was conducted at vegetable research centre, Patherchatta during winter season to find out the most suitable plant growth regulators and their appropriate concentration to increase the production of tomato. The trial was carried out in R.B.D with three replications. Seven different plant growth regulators (Alar, Ethephon, Cipa, GA3, 2,4-D, NAA, Paclobutrazol ( each with two concentrations such as 50 and 100ppm; 50 and 100ppm; 10 and 20ppm; 10and 20ppm; 5and 10 ppm; 20and 40ppm; 10and 20 ppm respectively) and control (water) were used as foliar spray at 30, 45 and 60 days after transplanting of the seedlings of the cultivar â€œPant T-3â€. All the P.G.R. reduced the plant growth than control except GA 20 ppm which was at par . CIPA 20ppm, Paclobutrazol 20 ppm and 2, 4-D 10 ppm reduced plant height significantly. Number of branches increased by Alar 100ppm, Naa 40ppm and Ethephon 100ppm while 2,4 D 10 and 5 ppm ; CIPA 20 ppm and Ethephon 100 ppm showed early maturity of fruits. More number of fruits per plant was recorded in CIPA 20 ppm, 2-4 D 5 ppm and NAA 40ppm. The percent fruit set was higher in CIPA 20ppm, 2, 4-D 5 ppm and GA3 10 ppm than control. Equatorial fruit diameter was greater in 2, 4-D 5 ppm, CIPA 20 and 10 ppm whereas polar diameter was higher in Ethephon 100 ppm, Alar 100 ppm and CIPA 10 ppm. More no of locules per fruit was higher in 2, 4-D 5 ppm and CIPA 20ppm on the other hand, NAA 40ppm, 2, 4-D 10ppm and paclobutrazol 20 ppm showed higher TSS and pericarp thickness was greater in Ethephon 50 ppm, NAA 40 ppm, 2, 4-D 5 ppm and CIPA 20 ppm. The lowest leaf curl virus infection was recorded in 2, 4-D 50 ppm (40%), 2, 4-D 10 ppm (45%) and NAA 40 ppm (68.3%). The highest fruit yield per plant was recorded in CIPA 20 ppm, 2 4-D 5 ppm and Alar 50 ppm and maximum fruit yield was recorded in CIPA 20 ppm, 2, 4-D 5 ppm and Alar 50 ppm which showed 71.47, 40.1 and 33.2% higher yield over control, respectively.